KOMPOSISI VISUAL TRAILER FILM KARTINI 2017 - Martinus Eko Prasetyo; Shierly Everlin (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2025)
AbstractThis study discusses the visual composition in the trailer of the film Kartini (2017), focusing on color, lighting, and spatial elements in the film’s visuals. It is crucial to understand how the visual elements in each scene are technically created as a medium of communication to convey messages to the audience. The primary objective of this research is to analyze the visual elements utilized in the trailer to construct the narrative, atmosphere, and technical aspects of the visuals. The research method employed is qualitative visual analysis, encompassing observations of cinematography, lighting, color, camera angles, and visual symbols. The findings reveal that the Kartini trailer strategically employs visual elements to depict the colonial-era atmosphere in Java, highlight social conflicts, and reinforce Kartini's characterization as the main figure. The use of warm tones, natural lighting, and dominant close-up shots effectively emphasizes Kartini's emotions and struggles. Additionally, the representation of Javanese cultural symbols enriches the visual narrative, thereby providing a unique appeal to the audience.